Primary malignant melanoma of oral mucosa - Report of two cases - S N Chandan; Sahith Kumar Shetty; B V Deepa (Wolters Kluwer Medknow Publications, 2020)
Primary malignant melanoma of oral mucosa is a rare and aggressive tumor. It is usually seen in the 5th and 6th decades of life. Its mainstay of treatment is surgery. It has a very poor prognosis, which is attributed to its late detection and distant metastasis. Dentists are often the first clinicians to come across these lesions and need to be able to identify them at the earliest for a better prognosis. In this article, we present two cases of extensive primary malignant melanoma of the oral cavity. Clinically, both the cases had a similar appearance of grayish-black pigmented nodular swelling on the buccal aspect and grayish-black discoloration on the palatal aspect. There were no significant radiological changes in both cases, indicating the superficial spread of the lesion. A positron emission tomography scan was performed in the second patient, which did not show any distant metastasis. Surgery was advised as a treatment for both the patients.